Impact of Organizational Commitment on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable in Transportation Companies in Sidoarjo, Indonesia - Silvya Makhfudho; Rifdah Abadiyah (Indonesian Journal of Law and Economics Review, 2019)
This study aims to determine the effect of Competency and Organizational Commitment on Employee Performance through Organizational Citizenship Behavior (OCB) at PT. Mentari Trans Nusantara in Sidoarjo. The analytical tool used is tabulating the questionnaire, collecting data in the form of a validity test and a reliability test. The hypothesis in this study is that there is an influence of Competence and Organizational Commitment on Employee Performance. There is an influence of Organizational Competence and Commitment on Organizational Citizenship Behavior (OCB). There is an influence of Organizational Competence and Commitment on Employee Performance through Organizational Citizenship Behavior (OCB). To test this hypothesis a data analysis tool is used in the form of a t-statistic test. The results obtained by the validity test showed that all statements were said to be valid. And for the reliability test of all variables is said to be reliable. For the hypothesis test based on the t-statistic test showed that there was a significant influence between competence and organizational commitment on Organizational Citizenship Behavior (OCB) and Employee Performance.